The Role Of Teachers In Enhancing Academic And Non-Academic Achievement Of Students At Madrasah Aliyah Miftahussalam Medan - Anisah Fitri, Ayu; Panggabean, Hadi Saputra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Teachers have a central role in determining the success of education in schools, teachers are required to be more active and strategic in encouraging academic achievement while developing students' non-academic potential so that they are able to compete and adapt in various situations. There are two objectives in this study, namely: 1) To determine the role of teachers in improving academic and non-academic achievement of students at Madrasah Aliyah Miftahussalam Medan. 2) What are the supporting and inhibiting factors for teachers' success in improving academic and non-academic achievement of students at Madrasah Aliyah Miftahussalam Medan. This research method uses a qualitative descriptive approach as a way to find data. Data collection techniques are used through observation, interview, and documentation methods. The results of this study indicate that teachers have an important role in the world of education as educators, mentors and motivators who greatly influence the improvement of student achievement both in academic aspects such as exam scores and non-academic aspects such as social skills and creativity. Teacher support in directing students to provide motivation, as well as guidance for extracurricular activities plays a very significant role in the overall development of students. Emphasizing the importance of the active role of teachers in creating a comfortable learning environment to support the achievement of students' academic and non-academic achievements.